1993
DOI: 10.1128/aem.59.7.2041-2048.1993
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Bacterial Growth on Chlorinated Aliphatic Compounds

Abstract: With the pure bacterial cultures Ancylobacter aquaticus AD20 and AD25, Xanthobacter autotrophicus GJ1O, and Pseudomonas sp. strain AD1, Monod kinetics was observed during growth in chemostat cultures on 1,2-dichloroethane (AD20, AD25, and GJ1O), 2-chloroethanol (AD20 and GJ10), and 1,3-dichloro-2-propanol (AD1). Both the Michaelis-Menten constants (Ki) of the first catabolic (dehalogenating) enzyme and the Monod half-saturation constants (Ks) followed the order 2-chloroethanol, 1,3-dichloro-2-propanol, epichlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…The half-saturation constant, K s , defines the ammonia uptake characteristics of different AOB species. Low half-saturation constants indicate a high affinity for ammonia and thus the ability of the AOB species to thrive under nutrient-depleted conditions (Lobban & Harrison, 1994;van den Wijngaard et al, 1993). Stehr et al (1995) reported K s values (NH 3 + NH 4 + concentration at which the halfmaximum oxidation rate was measured) ranging from 0.42 to 1.05 mg/L N for three Nitrosomonas oligotropha strains isolated from estuary sediment.…”
Section: Definition and Construction Of Nitrification Potential Curvesmentioning
confidence: 99%
“…The half-saturation constant, K s , defines the ammonia uptake characteristics of different AOB species. Low half-saturation constants indicate a high affinity for ammonia and thus the ability of the AOB species to thrive under nutrient-depleted conditions (Lobban & Harrison, 1994;van den Wijngaard et al, 1993). Stehr et al (1995) reported K s values (NH 3 + NH 4 + concentration at which the halfmaximum oxidation rate was measured) ranging from 0.42 to 1.05 mg/L N for three Nitrosomonas oligotropha strains isolated from estuary sediment.…”
Section: Definition and Construction Of Nitrification Potential Curvesmentioning
confidence: 99%
“…Continuous cultures. Continuous cultivation of bacteria was done in a fermentor with a volume of 1 liter, which was filled with 750 ml of medium as described previously (23). Culture medium was supplied via silicon rubber tubes and a Cole-Parmer peristaltic pump, model 7554-30.…”
Section: Methodsmentioning
confidence: 99%
“…cus GJlO is capable of utilizing DCE and other haloalkanes that are structurally related to DCE (e.g., 1-chlorobutane, 1-chloropropane, 1,3-dichloropropane, bromoethane) as the sole source of carbon and energy and was supplied by Dr. D. Janssen for use in this work (Janssen et al, 1985). The metabolic pathway of DCE degradation has been investigated and described by van den Wijngaard et al (1993).…”
Section: Source Of Microorganisms Xanthobacter Autotmphi-mentioning
confidence: 99%